1997
DOI: 10.3354/dao031141
|View full text |Cite
|
Sign up to set email alerts
|

Yellow-head virus:a rhabdovirus-like pathogen of penaeid shrimp

Abstract: Yellow-head virus (YHV), a highly virulent virus of cultured penaeid shrimp, was originally isolated from the black tiger shrimp Penaeus monodon in Thailand. It was initially described as a baculovirus, but was recently reported to be a n RNA-containing virus. The present study reaffirms the genome of highly purified YHV to be an unsegmented single-stranded RNA with negative polarity and of approximately 22 kb size. When analysed by SDS-PAGE, the purified virus yielded at least 4 viral structural proteins of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 6 publications
1
69
2
Order By: Relevance
“…TEM of negatively stained, purified YHV virions revealed spike-studded, enveloped particles measuring 150-170 X 40-50 nm (Wongteerasupaya et al 1995). The complete virion has an electron-dense nuclear core that measures 20 to 30 nm in diameter and is surrounded by a trilarninar envelope (Nadala et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEM of negatively stained, purified YHV virions revealed spike-studded, enveloped particles measuring 150-170 X 40-50 nm (Wongteerasupaya et al 1995). The complete virion has an electron-dense nuclear core that measures 20 to 30 nm in diameter and is surrounded by a trilarninar envelope (Nadala et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The 135 kDa polypeptide was glycosylated and was likely to be the viral glycoprotein (Nalada et al 1997). Based on size, bacilliform morphology, cytoplasmic replication, and the fact that it was a n ssRNA virus, YHV was proposed to b e a member of the Rhabdoviridae (Nadala et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Wongteerasupaya et al (1995) demonstrated that YHV contains a singlestranded RNA genome. Nadala et al (1997a) subsequently showed that the YHV genome is -22 kb long and identified 4 major virion proteins (170, 135, 67 and 22 kDa) of which the 135 kDa protein is glycosylated. Tang & Lightner (1999) have amplified reverse transcription-polymerase chain reaction (RT-PCR) products from cDNA synthesised using a primer of opposite sense to a putative coding sequence to show that YHV genomic RNA is likely to be of positive polarity.…”
Section: Introductionmentioning
confidence: 99%
“…The use of polyclonal antisera to detect YHV and white spot sydrome virus (WSSV) has been recently reported (Nadala et al 1997). However, the assay (Western blot analysis) was not highly sensitive and could not be easily applied during field examinations.…”
mentioning
confidence: 99%